Modifikasi Pembalut Wanita Berbasis Serabut Pelepah Sawit dan Serabut Kelapa Higienis dan Ramah Lingkungan - Eva Saputri Setyowati; Regina Tesa; Olif Syahbella; Riswandi; Sri Hilma Siregar (Sistem Informasi, 2022)
containing chlorine has a high risk of reproductive health for women, including the risk of: vaginal discharge, itching, irritation and causing cancer. Permenkes No. 472/Menkes/Per/V/1996 chlorine is a hazardous substance which is toxic and causes irritation and itching. Therefore, its use in sanitary napkins is prohibited. In this study, the aim of this study was to obtain sanitary and safe sanitary napkins and to use palm frond waste which is usually just thrown away. This research was conducted using materials, namely palm midrib fibers and coconut fibers and added with betel leaf extract. This research was conducted by testing the absorbency of the sanitary napkins. How to test the pads by making 2 samples, namely pads without a mixture of palm midrib and coconut fiber and pads with a mixture of palm midrib and coconut fiber, and tested how much the pads can absorb liquid with the unit used is mL. After being tested, the results of this study were that the absorption capacity of the pads of palm midrib and coconut fiber was better than that of pads without palm and coconut fiber.